Fourth International Workshop on Mining Software Repositories (MSR'07:ICSE Workshops 2007) 2007
DOI: 10.1109/msr.2007.5
|View full text |Cite
|
Sign up to set email alerts
|

Defect Data Analysis Based on Extended Association Rule Mining

Abstract: This paper describes an empirical study to reveal rules associated with defect correction effort. We defined defect correction effort as a quantitative (ratio scale) variable, and extended conventional (nominal scale based) association rule mining to directly handle such quantitative variables. An extended rule describes the statistical characteristic of a ratio or interval scale variable in the consequent part of the rule by its mean value and standard deviation so that conditions producing distinctive statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Adrian Bachmann, et al, [9] explored the process data quality and characteristics which have an influence on the bug fixing process and the process quality as measured by the process data influence on the product quality. Shuji Morisaki, et al, [10] described the study to reveal rules associated with defect correction effort and describes the extracted rules like a higher severity defect requires greater correction effort; defects detected in coding unit testing, were easily corrected. Syed Nadeem Ahsan, et al, [11] …”
Section: Literature Reviewmentioning
confidence: 99%
“…Adrian Bachmann, et al, [9] explored the process data quality and characteristics which have an influence on the bug fixing process and the process quality as measured by the process data influence on the product quality. Shuji Morisaki, et al, [10] described the study to reveal rules associated with defect correction effort and describes the extracted rules like a higher severity defect requires greater correction effort; defects detected in coding unit testing, were easily corrected. Syed Nadeem Ahsan, et al, [11] …”
Section: Literature Reviewmentioning
confidence: 99%
“…If this is not possible, then at least somebody outside the research group should perform the manual verification [14]. It is also suggested that rigorous inspection and testing is applied to the source code and scripts that implement the analysis approach since wrong output might not necessarily be due to poor heuristics, but simply due to defective implementations [44]. Finally, researchers suggest normalization in many scenarios.…”
Section: Comments From 5 Papers]mentioning
confidence: 99%
“…Morisaki et al [14] proposed an extended association rule mining method that takes advantage of interval and ratio scale variables, instead of simply replacing them into nominal or ordinal variables. In the proposed method, an extended rule describes the statistical characteristic of quantitative variables (e.g.…”
Section: Related Work: Rule Mining In Software Engineeringmentioning
confidence: 99%
“…We used NEEDLE [14] as an association rule miner. To obtain an initial rule set (for applying rule reduction methods,) rules were mined from Mylyn v.1.0 dataset with threshold values: minimum support  support = .01 and minimum confidence  confidence = .75.…”
Section: Initial Rule Setmentioning
confidence: 99%